METHODOLOGY OF THE QUR'AN AND ITS TAFSIR BY THE MINISTRY OF RELIGION AFFAIRS OF THE REPUBLIC OF INDONESIA - Ferdiani, Nani; Said, Hasani Ahmad (State Islamic University of Datokarama Palu, 2023)
This article explain about methodology of the Qur'an and its Interpretation creation Indonesian Ministry of Religion. Based on the statement that for some Indonesians understand the Qurâ€™an in depth language original is something it doesn't easy. So in thing this The Ministry of Religion of the Republic of Indonesia presents a translation and interpretation in Indonesian. Method used in article this namely library research with analysis descriptive. Researcher find that method used in the book of the Qur'an and its commentary that is divide the verses in one sura be several groups of verses, determine the topic in each group of verses as the main theme, determine the sub-themes to break down the interpretation of a group of verses, namely translation, vocabulary, munasabah , asbÄb al-nuzÅ«l , interpretation, conclusion, and conclusion as well as outlining the interpretation of each of the sub-themes that have been prepared comprehensively. Method/source of interpretation used Interpretation of the Ministry of Religion namely method bi al-ma'á¹¡Å«r. The method of interpretation uses the taá¸¥lÄ«lÄ« method. The style of interpretation is the hidÄ'Ä« style and the Ê»Ilmi style . Keywords: RI Ministry of Religion, Methodology, al-Qur'an and its Interpretation